A Biomechanical and Evolutionary Perspective on the Function of the Lumbrical Muscle - Wang, Keming (2014)
The lumbrical muscles of the hand originate from the flexor digitorum profundus tendons and insert onto the lateral band of the extensor tendons. Owing to these movable attachments, the function of this muscle is difficult to visualize. To better determine the function of this muscle, we took a novel approach by considering its relative anatomy, biomechanical characteristics, and evolution. With the smallest physiological cross-sectional area in the upper extremity, the lumbrical muscles have weak motor function, which is only 1/10 of the interosseous muscle. Because it is spindle-rich, the lumbrical muscles play an important role in the sensory feedback of the distal interphalangeal, proximal interphalangeal and metacarpalphalangeal joints of the fingers. The first two lumbrical muscles have lower variation in anatomy and higher density of muscle spindles compared to the ulnar two lumbricals. Additionally, the index and long finger lumbrical muscles are innervated by the median nerve, which also innervates the thenar muscles of the thumb. Therefore, it is possible that the first two lumbricals are functionally more important than the two ulnar lumbricals, specifically for precision pinch movements.